The Culture Conundrum: Classroom Challenges in the Asian Millennium - Ramnath, Srinath (Scholar: Human Sciences, 2015)
―Those who know nothing of foreign languages know nothing of their own.‖ Johann W Goethe. This study will aim to highlight the importance of learning, understanding and assimilating cross cultural awareness and developing tolerance towards other cultures and cultural mores in the context of a technological explosion through the use of cyber-media and globalization. Firstly the importance of cultural understanding in an era of Free Trade Agreements (FTA) and how institutions and organisations will need to reinvent themselves will be discussed. This is necessary in order to become more competitive in order to survive in a world dominated by the emergence of Asian Economies as Powerhouses, given the economic recovery in Asia, much faster than in the West with more V shaped countries; which has led the west to use the term, Asian Millennium and the significance of the G 20 summit rather than the G8 of the past. The next focus will be on how the paradigm shift in business models has morphed, the example of ―Lenovo‖ and ―Siemens‖ models will be highlighted, where business no longer happens to be a brick and mortar industry where money alone matters. What matters more now is how businesses can realign their models to become more competitive as the challenges of globalization pose more demands on businesses and their ability to adapt to cross cultures and tune themselves. This study will argue that understanding cultures better and developing business models based on cross cultural awareness and tolerance will be the keys for both educational institutions and global corporations alike to succeed in the Asian Millennium and for the west to be aware of Asian cultures now!